Bacillus aryabhattai Mitigates the Effects of Salt and Water Stress on the Agronomic Performance of Maize under an Agroecological System - Henderson Castelo Sousa; Geocleber Gomes de Sousa; Thales Vinícius de Araújo Viana; Arthur Prudêncio de Araújo Pereira; Carla Ingryd Nojosa Lessa; Maria Vanessa Pires de Souza; José Marcelo da Silva Guilherme; Geovana Ferreira Goes; Francisco Gleyson da Silveira Alves; Silas Primola Gomes; Fred Denilson Barbosa da Silva (Agriculture, 2023)
The use of plant-growth-promoting rhizobacteria (PGPR) can be one option for mitigating the impact of abiotic constraints on different cropping systems in the tropical semi-arid region. Studies suggest that these bacteria have mechanisms to mitigate the effects of water stress and to promote more significant growth in plant species. These mechanisms involve phenotypic changes in growth, water conservation, plant cell protection, and damage restoration through the integration of phytohormone modulation, stress-induced enzyme apparatus, and metabolites. The aim of this study was to evaluate the growth, leaf gas exchange, and yield in maize (Zea mays L.—BRS Caatingueiro) inoculated with Bacillus aryabhattai and subjected to water and salt stress. The experiment followed a randomised block design, in a split-plot arrangement, with six repetitions. The plots comprised two levels of electrical conductivity of the irrigation water (0.3 dS m−1 and 3.0 dS m−1); the subplots consisted of three irrigation depths (50%, 75%, and 100% of the crop evapotranspiration (ETc)); while the sub-subplots included the presence or absence of B. aryabhattai inoculant. A water deficit of 50% of the ETc resulted in the principal negative effects on growth, reducing the leaf area and stem diameter. The use of B. aryabhattai mitigated salt stress and promoted better leaf gas exchange by increasing the CO2 assimilation rate, stomatal conductance, and internal CO2 concentration. However, irrigation with brackish water (3.0 dS m−1) reduced the instantaneous water-use efficiency of the maize. Our results showed that inoculation wiht PGPR mitigates the effect of abiotic stress (salt and water) in maize plants, making it an option in regions with a scarcity of low-salinity water.